Understanding the influence of business innovation context on intentions of enrolment in master education of STEM students: a multi-level choice model - Ana-Maria Zamfir; Adriana AnaMaria Davidescu; Cristina Mocanu (Humanities & Social Sciences Communications, 2024)
Abstract This article studies educational decisions, focusing on intentions of enrolment in master’s education of STEM bachelor students. Integrating human capital theory with concepts of cultural and social capital, we propose a two-level model for the choice of pursuing master’s degrees. First level (individual) includes factors covering individual habitus and organisational habitus (higher education institutions of bachelor students), while the second level (local) reflects the local business innovation environment. The proposed model was empirically tested on data collected from a sample of STEM and non-STEM bachelor students enroled in 10 public universities located in Romania. The results show that STEM students display a higher propensity to enrol in master's education, and the gap between STEM and non-STEM majors varies across regions. We find that educational decisions related to master’s degrees are shaped by local circumstances reflecting the business innovation intensity as more innovative business contexts are less conducive for enrolment of students in master programmes. In addition, the findings of the study show that local circumstances are not independent of the field of study when shaping students’ educational choices, highlighting the complex way in which individual and local levels factors interplay and shape educational decisions. STEM students’ propensity to enrol in master’s degrees is more influenced by the innovative business environment than other students. This study has implications for higher education policy and practice aiming to support longer educational careers in STEM.